Pengoptimuman Penjadwalan Perawat pada Instalasi Ruang Inap RSU Propinsi NTB Berdasarkan Preferensi Libur Menggunakan Pemrograman Linear Integer Nol-Satu - Koko Hermanto; Marwan Marwan; Mamika Ujianita Romdhini (Universitas Islam Negeri (UIN) Mataram, 2011)
Zero-one integer programming is a mathematical method to solve the scheduling problems, such as nurse scheduling (cyclic scheduling) using Branch and Bound method. In cyclic scheduling method every nurse will work over a period of time (n days) and will take place periodically. The aim of this research is to give an alternative nurses scheduling which optimize the preference of each nurse that maximize the nurses performance and maximize hospital service. This research divided into three steps. First observations for actual hospital schedule, the second stage, formulation the actual schedule into linear programming model and solving the problem. Last, the solution from second step, transformed into the real problems, that is job schedule for each hospital room. Based on the analysis results the optimal schedule are obtained which maximize the quality of assignment for each shift, regard the job load and job constrain. Furthermore, there are significant different of both scheduling in quality and fairness aspect, examine scheduling is more dominant. Meanwhile, in three other aspect of coverage, stability and stability, both of schedule has the same characteristics.